Respuesta :

Y + 6 = -3Y + 26
    -6             -6
Y= -3Y + 20
     +3y
4y = 20

Y=5

Answer:

y = 5

Step-by-step explanation:

We must solve y in the following equation.

y + 6 = –3y + 26

We'll try to get the terms with y on the left and the independent terms on the right by performing the opposite operation on both sides of the equation:

y + 6 -6 = –3y + 26 -6

y = -3y + 20

y +3y = -3y +20 +3y

4y = 20

Now lets isolate the y, always by performing the opposite operation on both sides of the equation:

4y /4 = 20 /4

y = 5